Improving Language Teaching and Learning Process with Dual Coding Theory Approaches - Citra Kurniawan; Shirly Rizki Kusumaningrum; Kee-Fui Turner Lam; Ence Surahman (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Dual coding theory (DCT) allows students to process information based on stimuli in the form of visual-verbal signals. This study aims to measure the relationship between the implementation of DCT on the teaching and learning process. An experimental approach was used by involving 101 students. The results show that the DCT theoretical approach can be used to improve the language learning process. The research findings show that the learning strategies correlation coefficient is positive 0.826** which means that DCT has a very strong relationship with learning outcomes. In addition, the variables of gender and learning strategies have a positive relationship to learning outcomes with a positive correlation coefficient of 0.448**. Future studies are expected to consider several variables other than demographic variables.